The point - Lenzer, Norm; Nilsson, Harry; Beers, Carole; Wolf, Fred, 1933-; Good, Jerry; Gordon, Larry; Starr, Ringo; MVD Visual (Firm) (Oaks, PA : MVD Visual, 2012)
Tells the story of Oblio, a round-headed boy living in the land of "Point," where everything and everybody has one. Oblio, along with his trusty dog, Arrow, is banished to the Pointless Forest. Once there, the adventure begins. The tale is narrated by Ringo Starr and includes songs written and sung by Harry Nilsson.
Songs include Everything's got 'em -- Me and my arrow -- Poli high -- Think about your troubles -- Life line -- P.O.V. waltz -- Are you sleeping?
Originally released as a motion picture in 1971.
Story by Harry Nilsson and Carole A. Beers; produced by Jerry Good, Larry Gordon, Harry Nilsson, Fred Wolf.
Narrated by Ringo Starr.
Not rated.
DVD, stereo.
English audio.
Keywords: Individual differences -- Juvenile films; Social perception -- Juvenile films; Individuality; Feature films; Animated films; Children's films; Juvenile works